Faktor-faktor yang mempengaruhi budgetary slack - Pramudiati, Ningrum; Erlinawati, Afida (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2021)
This research aims to determine the effect of budgetary participation, budget emphasis and information asymmetry on budgetary slack at the OPD of Sleman. This research uses primary data in the form of a questionnaire. The study sample is 60 respondents involving employees on the OPD of Sleman engaged in the budgeting process. The sample selection uses a purposive sampling method with criteria, namely the head of office/agency, the director of finance, the chief of planning and planning staff who have a term of office at least one year. The data analysis used was the SPSS Version 26 with hypothesis testing using multiple linear regression. This study showed that indicate budgetary participation has no effect on budgetary slack on the OPD of Sleman. Still, the budget emphasis and information asymmetry have a significant positive impact on budgetary slack on the OPD of Sleman.